Budapeste: a legitimação do romance no meio literário. - Silva, Georgiana Coelho Santos (2012)
This paper discusses the trajectories that the novel Budapeste, by Chico Buarque drew toward its literary legitimacy. For this purpose we discuss the concepts and implications of the canon, as well as its movements. We investigate, from Michel Foucault, the authorship principle and possible responsibility of this authorship regarding the legitimacy of Budapeste book. Also confront the discourse of literary criticism in newspapers of national importance at the time of the Budapeste book launch, to identify, according to this discourse, the ways of legitimacy of the novel.